Access to healthcare: a promise fulfilled? A hoax? Or, a matter of control? A qualitative study into the experiences of international students in Hungary - Atiku, Livia Yawa Like; Adofo, Emmanuel (Frontiers in Public Health, 2025)
BackgroundWhile several studies have examined issues affecting international students in various settings on a global scale, there is a notable lack of evidence about international students in Hungary, and few or no studies have involved these students to better understand their needs. This study aimed at exploring the perspectives of international students on their self-assessed health status, access to healthcare services, and difficulties encountered in Hungary by distilling existing information on how studying in a foreign country has influenced their mental health and general wellbeing.MethodThe study was conducted to extract useful information relevant to the phenomenon from participants in video-recorded focus group discussions (FGDs). Six (6) FGDs were held, hosting students from two universities. A total of 21 international students were purposively sampled. International students aged between 22 and 38 years got featured [x¯ = 27 years, standard deviation (SD) = 4.322]. In general, questions were asked in relation to participants’ stay in Hungary and their experiences while engaging with clinic and hospital staff. Themes that emerged from discussions were analysed by thematic analysis of the transcripts.ResultsAlthough a comprehensive health insurance covered international students—Stipendium Hungaricum scholarship holders, some had difficulty accessing healthcare services and paid for medications prescribed to them when they thought otherwise. Other related challenges included linguistic barriers to effective communication with service providers, insensitivity, and a lack of empathy from some care providers toward the plight of migrant students. Additionally, there were negative attitudes from some service providers and a tendency toward cold abandonment, as well as concerns about the host nation’s perceived unpreparedness to receive them. This followed pockets of inconsistencies in the form of rigid bureaucracy, delays in responding to email requests for appointments with general practitioners (GPs), long waiting times, and issues of privacy and confidentiality.ConclusionEssentially, participants demonstrated they were aware of the guidelines for hospital consultations with a general practitioner (GP). The majority of international students, especially Stipendium Hungaricum scholarship holders praised the healthcare package that was advanced them. However, access to healthcare, which is central to Sustainable Development Goal 3 (SDG3), may be an illusion for some of these students, as the study revealed several obstacles hindering the smooth flow of processes in their quest for satisfactory healthcare. Therefore, this study emphasizes the need for improved systems (infrastructural and human resource capacity building) for a more efficient service.